(untitled) (International Conference on Multidisciplinary Sciences and Educational Practices, 2025)
In this article we discussed the equivalence of proverbs with flower component in English and Uzbek languages. Comparative- contrastive analysis was used to find differences and similarities of proverbs with flower component in the two languages